2012
DOI: 10.21307/joss-2019-027
|View full text |Cite
|
Sign up to set email alerts
|

Interorganizational Collaboration in the Hurricane Katrina Response*

Abstract: In this paper, we employ archival materials from multiple institutional sources to reconstruct the dynamic network of interorganizational collaboration that emerged in response to the Hurricane Katrina disaster of late 2005. Over the period from initial storm formation through the first week following landfall in Louisiana, we record active participation by over 1,500 organizations in response activities. We here conduct an exploratory analysis of the growth and evolution of the network of collaboration among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 29 publications
0
29
1
Order By: Relevance
“…have identified the complexities and subsequent challenges in this domain. Notable disasters such as Exxon Valdez, World Trade Center Attacks, Indian Ocean tsunami, Hurricane Katrina, and Haiti earthquake have highlighted failures in interorganizational collaboration (Butts, Action, & Marcum, ; Comfort & Kapucu, ; Kapucu, ; Nolte & Boenigk, ; Raju & Becker, ; Topper & Carley, ). Recent disasters such as Hurricane Maria continue to point toward failures of collaboration between organizations (FEMA, ).…”
Section: Emergency Management Collaborationmentioning
confidence: 99%
See 2 more Smart Citations
“…have identified the complexities and subsequent challenges in this domain. Notable disasters such as Exxon Valdez, World Trade Center Attacks, Indian Ocean tsunami, Hurricane Katrina, and Haiti earthquake have highlighted failures in interorganizational collaboration (Butts, Action, & Marcum, ; Comfort & Kapucu, ; Kapucu, ; Nolte & Boenigk, ; Raju & Becker, ; Topper & Carley, ). Recent disasters such as Hurricane Maria continue to point toward failures of collaboration between organizations (FEMA, ).…”
Section: Emergency Management Collaborationmentioning
confidence: 99%
“…The role of interorganizational collaboration between the nonprofit and public sectors was not immune to this scrutiny. Butts et al () reconstructed the dynamic network of interorganizational collaboration in the nonprofit and public sectors that emerged in response to Hurricane Katrina. This article identified that an enabler of collaboration was the role of a prominent nonprofit organization, the American Red Cross.…”
Section: Emergency Management Collaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…Staying abreast of alters' needs in an unpredictable environment and increased volumes of information individuals must process and transmit to others ultimately limit the amount of effort one can devote to supporting nonessential communication channels. These elevated cognitive burdens enhance the likelihood that individuals will become overwhelmed and engage in local network adaptation, a common response to disrupted task environments as individuals discard traditional roles and procedures as necessary in order to address the demands of their new task environment (Dynes, 1970;Carley, 1992;Butts et al, 2012;Comfort, 2007). Additionally, such environments frequently induce sense breaking in individuals (Maitlis & Christianson, 2014), in which individuals challenge their assumptions about the way the world (or, at least, their organization) works.…”
Section: The Impact Of Disruptionmentioning
confidence: 99%
“…Furthermore, despite the increasing prevalence of work on social media use in disasters, there have been only a few efforts (e.g., Li & Zobel, 2016) that look at social media in such a business context. Improving capabilities for capturing dynamics for situational awareness for agency or government decision-making agents (Butts, Acton, & Marcum, 2012;Petrescu-Prahova & Butts, 2008) could leverage social media data and physical sensors used by transportation and power engineers. This requires methods to validate the socially-generated data and ensure its accuracy and relevance.…”
Section: Opportunities and Challenges For Evacuation Dynamicsmentioning
confidence: 99%